A study on the adhesive properties of Cor. diphtheriae and Cor. parvum in the direct haemagglutination reaction - Ermolayev, A V; Fish, N G; Birger, M O; Sanzhakova, I E; Lobanova, A N (Journal of hygiene, epidemiology, microbiology, and immunology, 1987)
The adhesive properties of one Cor. parvum and two Cor. diphtheriae strains were investigated by means of the direct haemagglutination reaction (HAR). Using a specifically developed HAR procedure, it was proved beyond doubt that the studied Corynebacteria possess adhesive properties apparently associated with the presence of pili (fimbrias) on their surfaces. In addition, a correlation was found between the agglutinating activity of bacteria and the conditions of culture growth. Based on the reported results, it is suggested that there exists an intraspecies stability of adhesive properties and a possible link between corynebacterial adhesins and reticulostimulin.
Keywords: Rabbits; Corynebacterium diphtheriae; hemaglutinace; Guinea Pigs; Bacterial Adhesion; Propionibacterium acnes; skot; zvířata; Hemagglutination; Hemagglutination Tests; Cattle; trypsin; bakteriální adheze; Trypsin; Swine; Formaldehyde; formaldehyd; prasata; hemaglutinační testy; Animals; králíci; morčata